2022
DOI: 10.1111/bph.15775
|View full text |Cite
|
Sign up to set email alerts
|

A carvedilol analogue, VK‐II‐86, prevents hypokalaemia‐induced ventricular arrhythmia through novel multi‐channel effects

Abstract: Background and Purpose QT prolongation and intracellular Ca2+ loading with diastolic Ca2+ release via ryanodine receptors (RyR2) are the predominant mechanisms underlying hypokalaemia‐induced ventricular arrhythmia. We investigated the antiarrhythmic actions of two RyR2 inhibitors: dantrolene and VK‐II‐86, a carvedilol analogue lacking antagonist activity at β‐adrenoceptors, in hypokalaemia. Experimental Approach Surface ECG and ventricular action potentials (APs) were recorded from whole‐heart murine Langendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Hypokalemia can cause abnormal membrane potential of myocardial cells, which makes patients prone to potentially fatal arrhythmia. [27][28][29][30] In the present study, STEMI patients with MVA had a higher Killip class (OR=5.034, P=0.005), higher CK-MB levels (OR=1.002, P=0.022), and lower serum potassium levels (OR=0.618, P=0.020) compared with those without MVA, which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Hypokalemia can cause abnormal membrane potential of myocardial cells, which makes patients prone to potentially fatal arrhythmia. [27][28][29][30] In the present study, STEMI patients with MVA had a higher Killip class (OR=5.034, P=0.005), higher CK-MB levels (OR=1.002, P=0.022), and lower serum potassium levels (OR=0.618, P=0.020) compared with those without MVA, which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…It has been known for a while that dantrolene improved contractile function in patients with heart failure [ 161 ] and animal models of cardiomyopathy [ 31 , 162 , 163 , 164 , 165 ]. Accordingly, dantrolene reduced arrhythmias in patients [ 166 ] and different arrhythmia models [ 32 , 33 , 34 , 167 , 168 , 169 , 170 ]. Plenty of studies demonstrated that multisite RyR2 hyperphosphorylation plays a significant role in the pathogenesis of cardiac disease; however, it has long been a highly controversial area.…”
Section: The Ryr2 Channel As An Endogenous Target Of Dantrolenementioning
confidence: 99%
“…Action potentials and pseudo-ECGs were recorded simultaneously (methodology detailed previously). 2 Time to occurrence of the first spontaneous ventricular arrhythmia was compared between control and CPVT mice, at both concentrations of K 1 . The percentage of mice that developed ventricular arrhythmia was also compared between groups.…”
mentioning
confidence: 99%